March in memory of Dr. Martin Luther King Jr. [invitation] (1993)
Flier invitation that reads: 'The African American Student Union invites every to join our March in memory of Dr. Martin Luther King Jr. (January 15, 1929 - April 14, 1968)'. The invitation includes a photograph depicting a cake that reads 'Celebrating the 25th anniversary of Martin Luther King Jr.'.